PENERAPAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKANHASIL BELAJAR PADA MATERI MEMBACA PETA - Mandala, Riswanto; Hanifah, Nurdinah; Sudin, Ali (Jurnal Pena Ilmiah, 2019)
This research's objectives is to describe the implementation of scientific approach to improve learning outcome and maps comprehension in SDN Jatihurip. Scientific approach is very appropriate to be applied in the learning process in Indonesia The most important is the scientific study of scholarship in the learning process because it will improve the quality of learners by developing the element of knowledge attitudes and skills of students. Scientific method refers to the investigative techniques on one or several phenomena or symptoms, acquire new knowledge, or correcting and integrating previous knowledge. To be called scientific, the search method (method of inquiry) should be based on evidence of the object observable, empirical and measurable with the principles of the specific reasoning. Therefore, the scientific method generally includes a series of activities of collecting data through observation or experiment, process information or data, analyze and formulate and test hypotheses. While the steps are the steps: observe, ask, exploration, associate, communicate. Curriculum implementation in 2013 with the scientific approach should have been implemented since the early start of elementary school, because education is expected to have sustained did not break up with high school and college , if the implementation of this curriculum is true then the next 5 or 15 years Indonesia will be a great state to be able to compete with any country in the world.